Over a million students use our free study notes to help them with their homework
We know our answer is going to look like this: (ax + b)(cx + d). First we can split our original equation in order to make it easy to simplify. As we know that 12 multiplied by 3 is equal to 36 we c...
We will call sandwiches S and packets of crisps C. These are the 'unknowns'. From the information we can write down two equations. Equation 1: 3S + 2C = 9 and Equation 2: 5S + 6C = 19. We need two equatio...
Line A and line 4y+12x+24 are parallel. This means that they have the same gradient. In y=mx+c the gradient of the line is m. We can rearrange the equation 4y+12x+24 to find m. To begin with subtract 12x...
Substitute in the second equation into the first to eliminate x from the first equation. Solve for y which should, when solved (shown below), equal -5. Sub -5 back into either equation in the place of y t...
so we know that A+B+C= 72. We also know that B=2A (1) and C=3B which means C=6A (2) and with this information we can re arrange to equation to be only have one variable. so A+2A+6A= 72 Collecting all the ...
←
455
456
457
458
459
→
Internet Safety
Payment Security
Cyber
Essentials